Applying Ultrasonic Vibration to Decrease Drilling-Induced Delamination in GFRP Laminates - Mehbudi, P.; Baghlani, V.; Akbari, J.; Bushroa, A.R.; Mardi, N.A. (Elsevier, 2013)
Delamination is a major problem in drilling of fiber-reinforced composite materials. Thrust force is an important factor leading to propagation of delamination during drilling process. One of effective methods to reduce machining forces is application of ultrasonic vibrations. In this study ultrasonic assisted drilling is applied to reduce thrust force in drilling of GFRP laminates. In order to conduct experiments a setup is designed and fabricated to apply both vibrations and rotation to drill bits. Using Taguchi method, a set of experiments is conducted with feed rate, spindle speed, and ultrasonic vibration amplitude as control factors. The results show that applying ultrasonic vibration reduces the thrust force and therefore the drilling induced delamination dramatically.